Pengaruh Knowledge Management dan Entrepreneurship Orientation Terhadap Kinerja Organisasi - I Wayan Subawa; Ni Putu Eva Widnyani; Putu Kepramareni (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2026)
Strengthening organizational performance is a business strategy that leverages the benefits of new technologies. Creative resources are essential in the digital 4.0 era. Industries with unique products generally originate from rural creative ideas, but these appear to be disappearing due to technological advancements. The purpose of this study is to explore the changing role of human resource management by examining the role of Knowledge Management and Entrepreneurship Orientation on organizational performance. Hypothesis testing was conducted using Partial Least Squares Analysis with the help of the SmartPls application. Data collection was conducted through questionnaires. This study was a survey. The population was rural banks (BPRs) affiliated with Perbalindo and targeted by human resource development programs. The population in this study was all members of the BPR (Regional Banks) throughout Bali targeted by the program, comprising 160 BPRs in Bali, with an average employee size of 15, resulting in a total of 2,400 employees. Sampling was conducted using a random sampling method with a 5% sample size, resulting in a total sample size of 120 individuals spread across Bali. Capture fisheries competitiveness was analyzed using the PLS approach. The results of this study demonstrate that organizational performance is indeed influenced by knowledge management. Likewise, entrepreneurial orientation has a positive and significant impact on organizational performance.